Legal problems of institutionalisation of public-private partnership in the field of environmental protection - Makarova, Tamara I.; Kurylovich, Maria P. (Journal of the Belarusian State University. Law, 2023)
The article explores the possibilities of using public-private partnership in the field of environmental protection. The analysis of the Вelarusian and foreign legislation forms the statement that the cooperation between the state, business and the public is a partnership when certain legally significant conditions are met. And it is necessary to form its optimal legal framework and organisational structure (institutionalisation) for the implementation of such partnership in the Republic of Belarus. A distinction is made between two main approaches to the formation and implementation of public-private partnerships which are institutional and infrastructural. It is proved that the legislator of the Republic of Belarus in relation to public-private partnership generally adheres to the infrastructure approach, and in the practice of foreign states other methods of its organisation and implementation, including mixed, are used. The authors show the grounds for the formation of a public-private partnership in the legislation on environmental protection as an independent legal institution which based on the application of a mixed infrastructure-institutional approach, in particular, by concluding an agreement on joint activities (simple partnership).
Keywords: public-private partnership; environmental protection; environmental relations